Lg(x^3-5*x^2+3*x+21)=lg(x^3-6*x^2+4*x+27)

0 голосов
103 просмотров

Lg(x^3-5*x^2+3*x+21)=lg(x^3-6*x^2+4*x+27)


Математика (15 баллов) | 103 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

Lg(x³-5x²+3x+21)=lg(x³-6x+4x+27)
x³-5x²+3x+21=x³-6x²+4x+27
x²-x-6=0. x₁=-2, x₂=3
проверка:
x₁=-2.  lg((-2)³-5*(-2)²+3*(-2)+21)=lg((-2)³-6*(-2)²+4*(-2)+27)
lg(-23)=lg(-17) не имеет смысла (логарифмы отрицательных чисел не существуют)
х₂=3.  lg(3³-5*3²+3*3+21)=lg(3³-6*3²+4*3+27)
lg12=lg12
ответ: x=3

(276k баллов)